Cadastre for native land: a legal perspective from Malaysia and Indonesia - Liang, Toh Ming; Choon , Tan Liat; Seng , Looi kam; Vern, Tan Wee; Ujang, Muhamad Uznir bin; Chin , Thoo Ai; Ali, Nurlaila binti (International Journal of Psychosocial Rehabilitation, 2020)
Cadastre is an indispensable element in land administration system to facilitate the land development and urbanisation across the globe. In pursuing for a more advanced, sustainable, and technological cadastre system, many countries tend to neglect the existence of the traditional-based tenure system, the native customary tenure system. Inevitably, the integration of modern land administration systems with native customary tenure poses a huge challenge for most of the developing countries. Towards bridging the gap between the two, this study aims to provide insights regarding the legal framework of cadastre for native land; at the same time enables the comparison between Sarawak, Malaysia, and Indonesia with the overarching objective to provide enhancements for the current practices. Being descriptive in nature, this study adopts comparative case studies between Sarawak and Indonesia. Guided by a conceptual framework, the comparison consists of 10 best-practice indicators with 3 hierarchical level of specifications. The study revealed that there are sufficient land legislations regarding the cadastre practice for native land in Sarawak and Indonesia, but the efficiency is somehow impeded by the implementation gap between policy and actual practice. Towards the end of the paper, the recommendations are provided.